Long-term persistence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein-specific and neutralizing antibodies in recovered COVID-19 patients - Jira Chansaenroj (2022)
Understanding antibody responses after natural severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can guide the coronavirus disease 2019 (COVID-19) vaccine schedule, especially in resource-limited settings. This study aimed to assess the dynamics of SARS-CoV-2 antibodies, including anti-spike protein 1 (S1) immunoglobulin (Ig)G, anti-receptor-binding domain (RBD) total Ig, anti-S1 IgA, and neutralizing antibody against wild-type SARS-CoV-2 over time in a cohort of patients who were previously infected with the wild-type SARS-CoV-2. Between March and May 2020, 531 individuals with virologically confirmed cases of wild-type SARS-CoV-2 infection were enrolled in our immunological study. Blood samples were collected at 3-, 6-, 9-, and 12-months post symptom onset or detection of SARS-CoV-2 by RT-PCR (in asymptomatic individuals). The neutralizing titers against SARS-CoV-2 were detected in 95.2%, 86.7%, 85.0%, and 85.4% of recovered COVID-19 patients at 3, 6, 9, and 12 months after symptom onset, respectively. The seropositivity rate of anti-S1 IgG, anti-RBD total Ig, anti-S1 IgA, and neutralizing titers remained at 68.6%, 89.6%, 77.1%, and 85.4%, respectively, at 12 months after symptom onset. We observed a high level of correlation between neutralizing and SARS-CoV-2 spike protein-specific antibody titers. The half-life of neutralizing titers was estimated at 100.7 days (95% confidence interval = 44.5–327.4 days, R2 = 0.106). These results support that the decline in serum antibody levels over time in both participants with severe disease and mild disease were depended on the symptom severity, and the individuals with high IgG antibody titers experienced a significantly longer persistence of SARS-CoV-2-specific antibody responses than those with lower titers.